Settlement reduction of dredged marine soils (DMS) admixed with cement & waste granular materials (WGM): 1-D compressibility study - Rosman, Mohammad Zawawi; Chan, Chee Ming (2017)
Dredged marine soils (DMS) are considered as geo-waste and commonly disposed far into the sea. Environmental impacts raised from dredging such as turbidity and disturbance of marine ecosystem had increased the social demand to reuse DMS in engineering application. Typically, DMS have low shear strength and low bearing capacity. Hence, the DMS could be strengthened up by soil solidification. In present study, waste granular materials (WGM) such as coal bottom ash (BA) and palm oil clinker (POC) were utilized as additional binder to cement. The DMS were solidified with 3 series of admixtures; namely cement and/or WGM. The factor that influenced the compressibility of the soil sample such as percentages of admixtures were considered. Proportioned samples of 10, 15 and 20 % of cement, and/or 50 and 150 % of WGM of dry weight of DMS were subjected to one-dimensional oedometer test. The test samples were cured for 7 days in room temperature. Results show that cement- and WGM-admixed DMS have reduced the soil’s compressibility considerably than the untreated sample. As expected, the cemented soil had significantly reduced the settlement better than WGM-admixed soil. Hence, homogeneous samples of 15C50BA and 10C100POC produced almost similar reduction of compressibility as sample 20C. Therefore, reusing WGM as partial replacement of cement in DMS could provide beneficial reuse of these materials.